2009
DOI: 10.1007/s12010-009-8789-3
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Celecoxib Using Microbial Cultures

Abstract: Microbial transformation studies can be used as models to simulate mammalian drug metabolism. In the present investigation, biotransformation of celecoxib was studied in microbial cultures. Bacterial, fungal, and yeast cultures were employed in the present study to elucidate the metabolism of celecoxib. The results indicate that a number of microorganisms metabolized celecoxib to various levels to yield eight metabolites, which were identified by high-performance liquid chromatography diode array detection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Celecoxib is metabolized by many microbial species (2) and has broad antimicrobial activity against Gram-positive bacteria, as well as Gram-negatives when supplemented with membrane permeabilizing agents (3). Although inter-individual differences remained following treatment, the brief administration of the drug is a weakness of our study.…”
mentioning
confidence: 99%
“…Celecoxib is metabolized by many microbial species (2) and has broad antimicrobial activity against Gram-positive bacteria, as well as Gram-negatives when supplemented with membrane permeabilizing agents (3). Although inter-individual differences remained following treatment, the brief administration of the drug is a weakness of our study.…”
mentioning
confidence: 99%
“…This biotransformation method was done according to the reported method [40], with few modifications. Briefly, the second stage suspension cultures (25 mL) of all experimental organisms were added with racemic Carvedilol solution in methanol (0.01 mg/mL culture).…”
Section: Methodsmentioning
confidence: 99%
“…This process was repeated for three times and the combined organic phase was evaporated and dried in vacuum oven [40]. The residues were reconstituted with 1 mL methanol (HPLC grade), filtered through sterile filters (pore size-0.22 µm) and were analyzed by chiral HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…As interest in developing novel colon-targeted drug delivery systems for CRC has increased, insight into the presystemic biotransformation by the gut microbiota is fundamental. In vitro studies have shown that bacteria can metabolize celecoxib (14), potentially jeopardizing its anti-inflammatory effects. Additionally, whether celecoxib presence can modulate the host-microbiome crosstalk remains unresolved.…”
Section: Introductionmentioning
confidence: 99%